Child Development— A Psychological Perspective - Choudhary, Krishna Chandra; Mishra, Prabhat Kumar (THE PRIMARY TEACHER, 2018)
The period of early childhood, i.e., between three and six years of age, is the most crucial in an individual’s life. It is marked by rapid physical, psycho social and mental development. Children, particularly, in this age group, display curiosity, enjoy the company of peers and try to imitate adult behaviour. Hence, early childhood years need to be replete with friendly interactions with peers and family members so as to ensure the holistic development of the children. This paper reflects on the views of psychologists like Freud, Piaget, Skinner, etc., on various stages of child development. It also gives insight to various domains of child development, which would be useful for curriculum planners and developers, administrators, policy makers, educationists and teachers. It would help them to understand the different stages of child development and change in children’s behaviour patterns, particularly, at the primary level.